Correlation between Depressive Symptom Score and Geriatric Handgrip Strength at Nursing Home Province of Yogyakarta - Ahmad Syahri; Agus Siswanto; I Dewa Putu Pramantara (Faculty of Medicine Universitas Gadjah Mada, 2014)
ABSTRACTBackground: By the year of 2020, Indonesia’s elderly population will be expected to the fourth highest number in the world after China, India and USA. Special Region of Yogyakarta has the highest percentage that is equal to 13.72%. Depression may increase the risk of mortality, disability and motivation of physical Low grip strength would increase mortality and morbidity in the elderly.Objective: This study aimed to assess the correlation between depressive symptoms and handgrip strength in the elderly population in nursing homes at province of Yogyakarta.Methods: This study was a cross-sectional study that conducted in October 2010 at the nursing home residents. Depression was assessed by the Geriatric Depression Scale Cronbach’s alpha 0.88. Handgrip strength was measured by a handgrip dynamometer. Data of age, education and gender was collected by questionnaire. The study performed statistical tests to assess the correlation of symptoms depression and grip strength.Results: The mean age of subjects was 73.84 ± 8.36 years with 36 subjects (35.3%) were between 60-69 years and 66 subjects (64.7%) were over 70 years. There were 33 men (32.4%) and 69 women (67.6%). MeanGDS score was 12.76 ± 3.22. Handgrip strength in the depression group 16.94 ± 6.96 kg was higher than the non-depressed group 15.23 ± 6.79. There was correlation between severity of depression symptom byhandgrip strength with r = 0.235 (weak correlation) and statistically signifi cant with p = 0.017.Conclusion: The severity of depressive symptom scores was correlated significantly to the handgrip strength in elderly nursing homes in the province of Yogyakarta.Keywords: elderly, nursing homes, depression, handgrip strength.confi dent interval.